Efficacy of FOLFOX in Patients with Aggressive Pancreatic Neuroendocrine Tumors After Prior Capecitabine/Temozolomide - Al‐Toubah, Taymeyah (Oncologist, 2020)
BACKGROUND: 5‐fluorouracil, leucovorin, and oxaliplatin (FOLFOX) has activity in pancreatic neuroendocrine tumors (pNETs), but its use is limited, partly because of toxicities. pNETs can often become aggressive over time. We evaluated the efficacy of FOLFOX in patients with aggressive pNETs who had progressed after capecitabine plus temozolomide (cap/tem) among other treatments. MATERIALS AND METHODS: This was a retrospective study of all patients with well‐differentiated metastatic pNETs, treated at an academic cancer center between January 2008 and June 2019, who received FOLFOX and had received cap/tem in the past. The primary endpoint was objective response rate. RESULTS: Thirty‐one patients met eligibility criteria. Twenty‐five received FOLFOX, and six received FOLFOX with bevacizumab. Patients were heavily pretreated, having received a median of three prior lines of systemic therapy prior to FOLFOX (range, 1–8). Three (9.7%) patients had grade [G]1 tumors, 16 (51.6%) had G2, and 6 (19.4%) had G3, and grade was unspecified in 6 (19.4%) patients. Fourteen (45.2%) exhibited a best response of partial radiographic response per RECIST 1.1 criteria, 15 (48.4%) stable disease, and 2 (6.4%) progressive disease; overall response rate was 45.2% and disease control rate was 93.5%. Median progression‐free survival was 6 months (95% confidence interval [CI], 5.0–7.0), and median overall survival was 16 months from onset of study treatment (95% CI, 11.3–20.7) and 67 months from date of diagnosis (95% CI, 49.8–84.2). Median duration of treatment was 3 months, and median duration of response was 2 months. Toxicity profile was consistent with known adverse events associated with this regimen. CONCLUSION: FOLFOX is active in aggressive, heavily pretreated pNETs that have progressed on prior cap/tem chemotherapy; response durations are relatively short. IMPLICATIONS FOR PRACTICE: FOLFOX chemotherapy has robust activity in patients with rapidly progressive, heavily pretreated pancreatic neuroendocrine tumors (NETs), a setting in which few, if any, other options are likely to be effective. Durations of response, however, are relatively short, and new treatments are urgently needed for patients with aggressive transformation of pancreatic NETs.